Revelation - Fee, Gordon D. (Eugene, Oregon : Cascade Books, 2011)
"Revelation is a book that many Christians find confusing due to the foreign nature of its apocalyptic imagery. It is a book that has prompted endless discussions about the 'end times' with theological divisions forming around epicenters such as the rapture and the millennium. In this book, award winning author Gordon Fee attempts to excavate the layers of symbolic imagery and provide an exposition of Revelation that is clear, easy to follow, convincing, and engaging. Fee shows us how John's message confronts the world with the Revelation of Jesus Christ so that Christians might see themselves as caught up in the drama of God's triumph over sin, evil, and death. Fee draws us into the world of John and invites us to see the world through John's eyes as the morbid realities of this world have the joyous realities of heaven cast over them. In this latest installment in the New Covenant Commentary Series we see one of North America's best evangelical exegetes at his very best"--Publisher description.
The introduction (Revelation 1) -- The letters to the seven churches (Revelation 2-3) -- Fusing the horizons : Christ and his church(es) -- John's vision of heaven and earth (Revelation 4-6) -- Fusing the horizons : getting one's priorities in order -- An interlude in two parts (Revelation 7) -- The blowing of the seven trumpets (Revelation 8-11) -- The Holy War is engaged (Revelation 12:1-14:13) -- Prelude to the (original) tale of two cities (Revelation 14:14-20) -- The seven bowls of God's wrath (Revelation 15-16) -- The (original) tale of two cities, part 1 : the demise of Rome (17:1-19:10) -- The last battle and the end of evil (Revelation 19:11-20:15) -- The (original) tale of two cities, part 2 : God makes all things new (Revelation 21:1-22:5) -- Fusing the horizons : the original tale of two cities -- The wrap-up (or epilogue) (Revelation 22:6-21).
Vendor-supplied metadata.
Includes bibliographical references (pages 317-318) and index.
Master record variable field(s) change: 630
Keywords: Bible. -- Commentaries; Bible; RELIGION -- Biblical Studies -- New Testament; Openbaring van Johannes (bijbelboek); Electronic books; Commentaries